Monotone-iterative technique of Lakshmikantham for the initial value problem for a differential equation with a step function - S. G. Hristova; M. A. Rangelova (International Journal of Mathematics and Mathematical Sciences)
The initial value problem for a special kind of differential equations with a step function is studied. The monotone-iterative technique of Lakshmikantham for approximate finding of the solutions of the given problem is well grounded.